Using anonymized mobility data to reduce inequality in the availability and use of urban parks - Alessandro Filazzola; Garland Xie; Katie Birchard; Namrata Shrestha; Danny Brown; J. Scott MacIvor (People and Nature, 2024)
Abstract Parks are an integral component of cities. Ensuring city residents have equitable and easy access to parks is crucial for human well‐being. In temperate climates, park accessibility is particularly important in the summer months when these green spaces provide an area to recreate, exercise and escape indoor temperatures and heat emanating from paved and built surfaces. However, there are well‐known disparities in park accessibility in cities globally that may threaten the health of city residents, especially with global warming. We examined some of the largest city parks (>50 ha) in Toronto, Canada, by comparing park activity, housing demographics and daily weather patterns. We found that parks that provided more green space area per resident were situated in neighbourhoods that had higher proportions of single‐detached housing, higher automobile use and fewer multistorey apartments. We also found a strong correlation between park activity with population density and the number of amenities in the park. Surprisingly, we found no relationship between park activity and daily weather patterns, although park use was higher on weekends and holidays. These results suggest denser communities are at a disadvantage because they have proportionately less park area within walking distance in addition to having no private green spaces (e.g. backyards). We recommend revising municipal zoning around certain parks and the creation of new green spaces as methods to balance park provisioning in the city. Our findings suggest that designing and maintaining accessible, amenity‐rich parks is an important strategy for promoting health and well‐being in urban populations. Read the free Plain Language Summary for this article on the Journal blog.